Large bone defects in the tibia secondary to Aeromonas hydrophila infection in open fractures: Report of two cases - Juan Francisco Guio Oros; Estefanía Arias Cobos; Juanita Villalba Reyes; Jaime Andrés Leal (Trauma Case Reports)
This paper reports on two cases of post-traumatic osteomyelitis (OM) caused by Aeromonas hydrophila in immunocompetent patients, a rare but severe condition. A. hydrophila, a gram-negative bacterium typically found in aquatic environments, is seldom reported as a cause of OM. The first case involved a 42-year-old male with a Gustilo-Anderson grade II open tibial fracture exposed to sewer water, leading to persistent infection despite initial treatment. The second case described a 38-year-old male inmate with a gunshot-induced tibial fracture managed externally, later presenting with purulent discharge and bone exposure. Both cases required extensive surgical interventions, including multiple debridements, antibiotic therapy, and bone reconstruction using distraction osteogenesis techniques. This report emphasizes the importance of early suspicion of A. hydrophila infection in patients with open fractures and water exposure, noting that standard laboratory procedures may not routinely identify this pathogen. Effective management involves a combination of surgical and medical approaches, including targeted antibiotics and aggressive surgical debridement, with some cases necessitating amputation. The rarity of this infection and its challenging treatment underscore the need for further research to develop standardized protocols and improve clinical outcomes.